Sociodemographic characterization of domestic service workers in Colombia: a 10-year analytical-descriptive study - Oscar Espinosa; Zuly Bibiana Suárez-Morales; Valentina Álvarez; Valeria Bejarano; Mauricio Torres; Jairo Luna (Discover Social Science and Health)
Abstract Background Domestic workers have historically faced significant vulnerabilities globally. According to the International Labour Organisation, while their living and working conditions have improved over the years, challenges persist, particularly in guaranteeing their social protection rights worldwide. This research characterises the socio-demographic and labour conditions, as well as the social security coverage, of domestic service workers in Colombia between 2014 and 2023. Methods Using data from the Great Integrated Household Survey, we applied descriptive analytical techniques and statistical visualisation to explore the evolution of living and social security conditions (health, pension and occupational risk) over the last decade of domestic service workers in Colombia. This analysis was conducted by geographic-epidemiological region, sex and age group. Results Over 92% of domestic service workers are women, with child domestic labour persisting in rural areas, particularly in Oriental and Caribbean regions. These regions, along with the Amazon-Orinoquía, exhibit the highest informality rates. Social security coverage, while improving, remains insufficient, with less than 29% of workers affiliated with pension funds and under 25% covered by occupational risk insurance. Health insurance coverage reached 97% in 2023; however, most workers are in the subsidised regime, facing vulnerabilities. Educational attainment has increased, particularly in urban areas such as Bogotá-Cundinamarca and Pacific regions, where workers are more likely to have completed secondary education or higher. Despite these advances, wages remain precarious, often below the legal minimum wage. Conclusions Our analysis in Colombia of living and social security conditions of domestic service workers shows that those living and working in rural areas face worse living conditions, underscoring the need for the State to improve conditions that ensure decent work in the countryside. While progress has been made in improving social protection, and in expanding educational opportunities, further efforts are required. International comparisons reveal similarities with other developing nations, underscoring global challenges in gender, ethnicity, and labour rights.